Increased Frequency of Down Syndrome in Young Mothers of Rural Population - T. Lazar Mathew2, R. Regina Mary1, K.M.Gothandam2*, (Journal of Ecobiotechnology, 2010)
Studies were conducted in 222 children clinically diagnosed with Down syndrome (properly diagnosed on the basis of symptoms by Dr. Chandraleka, Pediatrician) to understand the frequency and type distribution of such cases; and to determine the origin of extrachromosome in the 21st pair. Clinical diagnosis was confirmed with karyotyping. Results have shown that nondisjunction or pure trisomy 21 appears to be the main cytogenetic cause; with a percentage frequency of 96.4%; comprising of 114 boys (53.3%) and 108 girls (46.7%). Also the cytological and molecular analysis result revealed that Down syndrome was increased in the young Indian mothers especially in the rural areas. -------------------------------------------------------------------------------------------------------- 1Department of Advanced Zoology & Biotechnology, Auxillium College, Vellore 2School of Bio Sciences & Technology, VIT University, Vellore â€“ 632014 <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">*Corresponding author, Email: gothandam@yahoo.com Please Cite This Article As: Â  R. Regina Mary, K.M. Gothandam, T. Lazar Mathew. 2010. Increased Frequency of Down Syndrome in Young Mothers of Rural Population. Journal of Ecobiotechnology 2/3: 40-44.